Innovative Transport Pressure Management Models for Efficient Transportation Management in the RUDN-University - Redina, Margarita; Savenkova, Elena; Khaustov, Aleksandr; Silaeva, Polina (Journal of Sustainability Perspectives, 2021)
The main transport flows on the RUDN territory are caused by the city public and private transport. The general transportation scheme around and through the campus develops some decades. Today this is a huge traffic system with high technogenic pressure on the surrounding ecosystems. The efforts of the university only on the organization of bike transport and shuttle buses cannot protect in this situation our territory. Thus, the university in collaboration with the Moscow government try to solve the transportation problem: a new underground station named RUDN will be built – this must help to optimize transport flows. Transportation management in the university campus (especially situated in the city) needs to apply reliable models for the optimization of transport pressure. That is why, for the RUDNUniversity campus in the South-West of Moscow, we try to develop the most sensitive indicators and to control a set of technogenic factors affecting environmental quality. The unique environmental monitoring system of the RUDN campus able to evaluate the environmental state of the territory and to contribute to maintaining the environmental quality is now under development. The primary results were presented in September 2019 during the first UI Green Metric World Sustainable Campuses Tour in RUDN.